SENSITIVITAS ANTIMIKROBA TERHADAP BAKTERI ESCHERICHIA COLI YANG DIISOLASI DARI UDANG DI PASAR KEPUTRAN SURABAYA - Rahmaniar, Reina Puspita; Widhowati, Dyah; Hidayah, Nurul (JURNAL KAJIAN VETERINER, 2019)
The aimed of this study was to identify antibiotic Resistance of Escherichia coli isolated from Shrimp. There were 20 samples taken and isolated on surface of Eosin Methilen Blue Agar. E.coli produced metalic green colonies. Samples identified as E.coli based on macroscopic features and morphology of colonies, microscopic examination with gram staining and biochemical tests. The antibiotic sensitivity was determined through a standard antimicrobial disk diffusion test. The results of this study showed that 9 samples were bacteria of the spesies E. coli. Based on the results of antibiotic sensitivity test, it was found that 100 % of E. coli isolates were resistant to Amoxycillin 20 µg and 22,2 % of isolates are resistant to ampicillin 10 µg. Antibiotics Tetracycline 30 µg and Chloramphenicol 30 µg were 100 % sensitive. Gentamicin 10 µg showed that 77,8 % sensitive and 22,2 % intermediet. The precence of antibiotic resistance of betalaktam antibiotics makes it especially important to monitor antimicrobial susceptibility and mechanisms of resistance of E.coli isolated from shrimp, because new mechanisms of resistance occurring in animals may enter the food chain and its be transferred to the human. This importance of cooperation between sectors in order to monitor antimicrobial resistance.